التجـــربة النقــدية عنــد عبــد الفتــاح كيليــطو بحـث في آليات التفكيـك و النقـد الثقافي - راوية برجم (My University, 2019)
Summary The contemporary Arabic Criticism experiment concentrated on openness to the western culture. This is what has become incarnate to the western critic Abd El Fatah Kilitto who devoted his efforts on questioning the old Arabic heritage with all its fields for restoring and knowing it, wherever the narrative has a complete luck fro; its criticism, so it has the care for studying “ One thousand nights and night” “Kalila and Dimna” stories and El Hamadani and El Hariri standing, concentring on careless fields in these deeds, so he presented it thanks to the skillfulness and accuracy of analysis. Also, he researched on the silence separating between the knowledge and using the new strategies. Also, he standed on some other traditional texts in philosophy or prose… with centre or margin, he studied some books of El Djahid, Ibn Rochd and Abi El Allaâ El Maâri in its general cultural context as cultural texts. Also, he was interested on the discussion of the problem of Arabic language so, he asked it in a special way of criticism, dividing the different knowledge’s wherever he came back to deep history to become familiar with the subject, so he treated the first language; the language of Adam (peace be upon him) and the heritage language…etc. He arrived to the past with the present, so he concentrated on language as one of the present problems that has a relation with the nationality, the personality, the other personality, be languages and translation, so he dealt with it starting from as it is a personal problem to be discussed with the western literature that is expressed in foreign language, for this, the research of Kilitto is considered a research for the existence and personality in language. And the occupation of the critic with these subjects has made his critical way changing from old to new. Kilitto was able to improve his goodness in comparison, analysis and explanation, thus with his arms of the knowledge extracted from the western criterion methods like cultural criticism…and evolving it with the special Arabic texts. The excellence of the critic experiment occurs on the Arabic and western culture both and its openness to a lot of foreign languages. ---------------------------------------------------------------------------- مـلـخـص ارتكزت التجربة النقدية العربية المعاصرة على الانفتاح على الثقافة الغربية. و هذا ما تجلى لدى الناقد المغربي (عبد الفتاح كيليطو)، الذي كرّس جهوده لمساءلة التراث العربي القديم بمختلف أوجهه، من أجل إحيائه و التعريف به، حيث نال السرد حظا وافراً من مقارباته النقدية، فاهتم بدراسة قصص "ألف ليلة و ليلة" و "كليلة و دمنة" و مقامات كل من ا"لهمذاني" و "الحريري"، مركزا على جوانب مغيبة و مهمشة في هذه الأعمال، فقام بإبرازها بفضل براعة التحليل و دقة الاستنتاج. كما بحث في المسكوت عنه فاصلا بين المفاهيم و مستعملا آليات منهجية مستحدثة. و كذلك وقف عند بعض النصوص التراثية الأخرى سواء ما تعلق بالفلسفة أو الشعر... بالمركز أو الهامش، فدرس بعض مؤلفات الجاحظ و ابن رشد و أبي العلاء المعري ضمن سياقها الثقافي العام باعتبارها نصوصاً ثقافية. كما انصب اهتمام (كيليطو) أيضا على مناقشة قضية اللغة، فطرحها بطريقة نقدية متميزة،منقبا في مختلف المعارف، حيث عاد إلى أعماق التاريخ من أجل الإلمام بالموضوع، فتطرق إلى اللغة الأولى، لغة آدم عليه السلام و لغة المرثية و غيرها. و قد وصل الماضي بالحاضر فركّز على اللغة باعتبارها إحدى القضايا الراهنة المرتبطة بالهوية و الأنا و الآخر و الازدواجية اللّغوية و الترجمة، فتعرض لها انطلاقا من كونها مسألة شخصية، ليطرحها موازاة مع الأدب المغربي المعبر عنه باللغة الأجنبية، لذلك يعتبر بحث (كيليطو) في قضية اللغة بحثًا عن الوجود و الكيان و الذات. و انشغال الناقد بهذه المواضيع جعل مساره و توجهه النقدي يشهد تحوّلاً من القديم إلى الحديث. استطاع (كيليطو) أن يثبت جدارته في المقاربة و التأويل و التحليل، و ذلك بتسلحه بآليات و مفاهيم مستوحاة من النظريات و المناهج النقدية الغربية( كالتفكيك و النقد الثقافي و البنيوية...) و تطويعها وفق خصوصية النصوص العربية. و ينبع تميز تجربته النقدية و طرافتها أساسًا من الإلمام بالثقافتين العربية و الغربية على حدٍّ سواء، و انفتاحه على عدة لغات أجنبية و نبشه فيها بمعول التمثّل والوعي بتميز اللحظة و دقتها . ---------------------------------------------------------------------- Résumé L’expérience critique arabe contemporaine était fondée sur l’ouverture à la culture occidentale, ce que reflète le critique marocain Abdelfatah Kilito qui a consacré ses efforts à le responsabilité de l’ancien héritage arabe sons tous ses aspects, ainsi que d’autres textes culturels, que ce soit la philosophie ou la poésie… margé ou centré. Il s’est également concentré sur la discussion de certaines questions récentes telles que la langue, la duplication linguistique et la traduction, qui ont constitué un changement dans le cours et la direction de sa critique de l’ancien vers le moderne. Le critique a su prouver sa valeur dans l’approche, l’interprétation et l’analyse en l’armant de mécanismes et de concepts inspirés par les théories et les approches critiques occidentales. Son expérience critique découle principalement de sa connaissance des cultures arabe et occidentale, et de son ouverture à plusieurs langues étrangères.